Nut consumption in association with overall mortality and recurrence/disease‐specific mortality among long‐term breast cancer survivors. Issue 4 (19th October 2021) - Wang, Cong; Gu, Kai; Wang, Fei; Cai, Hui; Zheng, Wei; Bao, Pingping; Shu, Xiao‐Ou
Abstract: High nut consumption is associated with reduced total and certain cause‐specific mortality in general populations. However, its association with cancer outcomes among long‐term breast cancer survivors remains unknown. We examined the associations of nut consumption (including peanuts and tree nuts), assessed at 5‐year postdiagnosis, with overall survival (OS) and disease‐free survival (DFS) among 3449 long‐term breast cancer survivors from the Shanghai Breast Cancer Survival Study, applying Cox regression analysis. During a median follow‐up of 8.27 years post dietary assessment, there were 374 deaths, including 252 breast cancer deaths. Among 3274 survivors without previous recurrence at the dietary assessment, 209 developed breast cancer‐specific events, that is, recurrence, metastasis or breast cancer mortality. At 5‐year post dietary assessment (ie, 10‐year postdiagnosis), regular nut consumers had higher OS (93.7% vs 89.0%) and DFS (94.1% vs 86.2%) rates. After multivariable adjustment, nut consumption was positively associated with OS ( P trend  = .022) and DFS ( P trend  = .003) following a dose‐response pattern, with hazard ratios (95% confidence interval) of 0.72 (0.52‐1.05) for OS and 0.48 (0.31‐0.73) for DFS, for participants with greater than median nut intake compared with nonconsumers. The associations did not vary by nut type. Stratified analyses showed that the associations were more evident among participants with a higher total energy intake for OS ( P interaction  = .02) and among participants with early stage (I‐II) breast cancers for DFS ( P interaction  = .04). The nut‐DFS associations were not modified by estrogen receptor/progesterone receptor status or other known prognostic factors. In conclusion, nut consumption was associated with better survival, particularly DFS, among long‐term breast cancer survivors. Abstract : What's new? High nut consumption has been associated with reduced all‐cause and cause‐specific mortality. However, to date, nut intake has not been investigated for associations with survival outcomes among breast cancer patients. This large cohort study found that nut consumption among long‐term breast cancer survivors was associated with a 52% reduced risk of recurrence or breast cancer mortality following a dose‐response pattern. The association was stronger for survivors with stage I‐II breast cancer than those with stage III‐IV breast cancer. This study provides evidence for promoting nut consumption as a modifiable lifestyle factor among breast cancer survivors.